Folktale Animations with Sign Language as Cultural Literacy Materials for Deaf People - Hidayat, Herry Nur; Almos, Rona; Firmansyah, Okta (The Center for Disability Studies and Services Brawijaya University, 2025)
The absence of culturally relevant and accessible literacy materials for the deaf community is a pressing concern that has persisted due to the failure of existing materials to adequately address the unique needs of this demographic. This article expounds on the endeavors to mobilize and promote a culture-based literacy movement for people with disabilities, with a particular focus on Deaf community. In this context, cultural literacy is defined as the understanding and appreciation of a culture's values, beliefs, and practices and the ability to express and interpret these elements through various forms of communication. Visual media constitutes the predominant medium for cultural literacy promotion among Deaf community. The Minangkabau folktale is selected due to its cultural richness. Beyond the transmission of values and norms, folktales are believed to play a pivotal role in shaping and reinforcing the Minangkabau identity of Deaf community. The collection of Minangkabau folktales is curated based on its cultural values. The selected folktale is then adapted into illustrated stories and transformed into animations. These animations, when presented in sign language by JBI (Juru Bahasa Isyarat, or” Sign Language Interpreters”), who play a crucial role in translating the content into sign language, are expected to not only make the content accessible but also to inspire and empower Deaf community. The creation of these animated folktales is poised to serve as a model for enriching cultural literacy materials, particularly for Deaf people.